Compressive property and shape memory effect of 3D printed continuous ramie fiber reinforced biocomposite corrugated structures. (1st December 2022) - Cheng, Ping; Wang, Kui; Chen, Xuanzhen; Le Duigou, Antoine; Peng, Yong; Wen, Wei
Abstract: The present work aimed to study the quasi-static compression behaviors of 3D printed continuous ramie fiber reinforced biocomposite corrugated structures (CFCSs) with excellent shape memory effects. The in-plane compression test was conducted to evaluate the effects of cell shapes, fiber volume fraction ( f v ) and addition of fiber on the compression behaviors and energy absorption (EA) characteristics of the corrugated structures. The results showed that the compression property and EA capacity of the 3D printed CFCSs increased with decreasing f v and the addition of continuous ramie yarn. The 3D printed continuous ramie fiber reinforced biocomposite with inverted trapezoid cell shape corrugated structures (CFITCSs) outperformed other cell shapes in the compression strength and specific EA. The analytical model for the in-plane compression strength of CFITCSs was derived, and predictions were in good agreement with measurements. In addition, continuous natural fiber reinforced composite structure for shape memory was proposed for the first time. The shape recovery testing results demonstrated that 3D printed CFCSs had the potential to be a key element of lightweight programmable smart systems.